Pemanfaatan Lingkungan Sekitar untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik pada Muatan Pelajaran IPS - Giyato Giyato; Gunawan Sridiyatmiko (UM Purwokerto Press, 2022)
The focus of this research is the use of the environment around the school as a source of effective and efficient learning to increase learning motivation and student learning outcomes in social studies learning. The surrounding environment as a learning resource is very beneficial for the social studies learning process, this is because the learning resources are close to the students, so it is easier for students to understand the learning resources. Utilization of the environment as a learning resource is a method where the teacher invites students to study outside the classroom to see events directly in the field with the aim of familiarizing students with their environment. Through the use of the environment around the school, students are able to achieve better learning outcomes in social studies subject matter. Thus, the use of the surrounding environment as a learning resource can increase learning motivation and student learning outcomes. Recommendations that can be submitted: 1) It takes the expertise of teachers to design lesson plans that are in accordance with learning objectives and the environment around the school. 2) Before students take advantage of the surrounding environment, they should be equipped with scientific insight and social relations with the community as the basic basis for learning motivation.